Irrigation Management Practices for Wheat Production in the Gezira Agricultural Scheme, Sudan - Farah, S M; El-Award, O A; Salih, A A; Ali, I A (Annals of Arid Zone, 2016)
Assessment of the impact of the current irrigation practices of the Gezira Agricultural Scheme (GAS) by tenants with reference to wheat (Triticum aestivum) during two seasons was undertaken. Tenants were applying irrigation water either in excess or less than the crop water requirement (CWR). This might have been attributed to: (a) variation in water supply caused by weed infestation. silt deposition. and water indenting not based on the actual CWR. and (b) unawareness of the .tenants about the adverse-effects of over-irrigation. As such. the tenants who had good access to the water tended to over-irrigate their crops. thus putting the other users under water shortages. Such water management practices have resulted in application of 30 to 40% irrigation water in excess of the actual CWR and reduced crop yields. This excess water could have been easily used for increasing the area under wheat. In this regard some suggestions are proposed.